EU-Fiskalregeln - Anker oder Mühlstein der europäischen Wirtschaftspolitik? - Kitzmantel, Edith (Wirtschaft und Gesellschaft, 2016)
The EU fiscal rules were developed in the 90ies in preparation of EMU and were refined and reinforced in 2011 to 2013. In view of the high levels of public debt, budget consolidation is an important target. The chosen approach is in principle suited to be effective and to ensure equal treatment of Member States. However, the narrow focus on budget discipline at Member State level has had two major drawbacks: Equally important Treaty objectives (growth, employment, social justice) have been marginalised, and the fiscal stance at EU level has been arbitrary. Today European economic policy faces the dilemma that, with monetary policy having come to its limit, it does not possess a macro-economic instrument to break the vicious circle of „stagnation/insufficient growth – renewed consolidation effort“. There are two possible escapes: creating new instruments at Union level which provide a sufficient push to aggregate demand or enlarge Member States’ budgetary room for manoeuvre.